Nichtvirale sexuell übertragene Infektionen: Epidemiologie, Klinik, Labordiagnostik und Therapie : Teil 3: Treponemen, Gardnerella und Trichomonaden - Nenoff, Pietro; Helmbold, Peter (Der Hautarzt, 2017)
In Germany, the reported syphilis prevalence has increased continuously since 2010, with a total of 6834 syphilis cases being reported in 2015. The largest increase of reported syphilis occurred in men who have sex with men (MSM). The antibiotic agent of choice for treatment of syphilis is still penicillin. There are no penicillin-resistant Treponema pallidum strains. Alternatives are ceftriaxone and doxycycline. In Germany, azithromycin is not approved for treatment of syphilis; however, therapy failures are increasingly reported. Bacterial vaginosis is accompanied by vaginal discharge. The vaginal secretion exhibits an increased pH value higher than 4.5. Clinical symptoms are pruritus, burning, and the characteristic amine odor. The probability for bacterial vaginosis is highest in women with higher numbers of sexual partners, unmarried women, early first sexual intercourse, in commercial female sex workers, and those women who regularly apply vaginal douches. The main pathogen of bacterial vaginosis is Gardnerella vaginalis. For oral therapy metronidazole is given, alternatively clindamycin; the latter should be applied additionally as topical agent. Trichomoniasis is considered as the nonviral sexually transmitted infection with the highest prevalence worldwide. Other than direct microscopic detection of the protozoa (trophozoites) in vaginal secretion or urine, PCR has been approved as the diagnostic method with the highest sensitivity. Oral metronidazole represents the therapy of choice in trichomoniasis.
Gesehen am 03.05.2018